Phosphoinositide spatially free AKT/PKB activation to all membrane compartments. (May 2019) - Thapa, Narendra; Horn, Hudson Tyler; Anderson, Richard A.
Abstract: Ser and Thr kinase AKT also known as protein kinase B (PKB) was discovered more than two and half decades ago and is one of the key downstream molecules in the phosphoinositide 3-kinase signaling pathways. The pleiotropic effects of this kinase have attracted intense interest and limelight in cancer biology, cancer therapy, diabetes, and cardiovascular diseases. Authors may refer to other more comprehensive and recent reviews on AKT/PKB (Manning and Cantley, 2007; Manning and Toker, 2017). AKT/PKB is one of the most enigmatic and most studied signaling molecule in cancers and is a significant therapeutic target (Brown and Banerji, 2017). Yet, how AKT/PKB activation couples with its downstream target/substrate molecules that function in diverse subcellular compartments remains obscure. Recent studies indicate the continuous interaction of AKT/PKB with PI3, 4, 5P3 or PI3, 4P2 in a lipid membrane is required for its activation throughout the cells (Ebner et al., 2017). Here, we summarize the recent progress on the mechanism for phosphoinositide (PI3, 4, 5P3 and PI3, 4P2 ) spatial control of AKT/PKB activation on the plasma membrane and endomembrane compartments.